2018
DOI: 10.4236/ojer.2018.72005
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Correlation of Physiological and Psychological Health Hazards in Human Habitats with Seismicity, Mountain Air Turbulence and Environmental Infrasound

Abstract: A statistical correlation study on the basis of published data has been performed in order to find whether an abnormal degree of human physiological ailments and a psychology of sustained violent reactions in highly populated habitats are correlated with environmental infrasound emissions related to seismic activity and sustained by mountain air turbulence. The study focus is on Latitude 34˚ North coinciding with boundaries of colliding Tectonic Plates in three continents. Earthquakes, rock fractures and lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Hundreds of medical investigations worldwide bring out that exposure to infrasound at specific frequencies and amplitudes damage human metabolism and lead to a variety of serious psychological ailments; and (at higher infrasound amplitudes) physiological ailments as well like hearing disabilities. [3] revealed that the centuries of unresolved ethnic conflict existed not only in the Kashmir region at 34 degrees north latitude, but indeed over 10,000 kilometers of the Asian continent around this very same latitude along the boundaries of colliding tectonic plates. The one common geophysical feature was that the entire region along this latitude was highly seismic.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of medical investigations worldwide bring out that exposure to infrasound at specific frequencies and amplitudes damage human metabolism and lead to a variety of serious psychological ailments; and (at higher infrasound amplitudes) physiological ailments as well like hearing disabilities. [3] revealed that the centuries of unresolved ethnic conflict existed not only in the Kashmir region at 34 degrees north latitude, but indeed over 10,000 kilometers of the Asian continent around this very same latitude along the boundaries of colliding tectonic plates. The one common geophysical feature was that the entire region along this latitude was highly seismic.…”
Section: Introductionmentioning
confidence: 99%